4 Immune response evaluation to curative conventional therapy – The IRECT trial. Issue 5 (May 2015) - ,; Atanackovic, D.; Lütkens, T.; Lotfi, R.; Mytilineos, J.; Schuler, P.; Veit, J.; Hoffmann, T.K.
Abstract : Introduction: Cancer-testis antigens (CTA) are specifically expressed in different cancer types, but not in healthy normal tissue with the exception of testis. This tumor-restricted presence makes them an ideal target for specific cancer immunotherapy. In head and neck squamous cell carcinoma (HNSCC), CTA of the MAGE-A family and NY-ESO-1 have been identified as independent prognostic markers for poor survival. The addition of immunotherapeutic strategies targeting CTA may specifically improve the survival of this group of patients with an increased risk of death. To date little is known about the dynamics of CTA-specific immune responses during conventional treatment. Material and methods: The IRECT trial is a non-interventional, prospective clinical trial. Stage III/IV HNSCC patients who are treated with curative intent by surgery followed by (chemo-)radiation as indicated or by primary chemoradiation are monitored over the course of standard-of-care treatment for HNSCC. Tumor tissue is being collected at the time of diagnosis. Serum, plasma and peripheral blood mononuclear cells (PBMC) are collected at defined time points before and during treatment and at every follow-up after treatment for the first 12 months. Results: Patient recruitment started 09/2013 at the University Medical Center Ulm. To date 13 patients have been included into the trial. The primary sites were oropharynx (6/13), larynx (2/13), hypopharynx (1/13) and oral cavity (4/13). Five patients had stage III, 7 stage IVa and 1 patient stage IVb disease. Eleven patients were treated by primary surgery and 2 patients received primary chemoradiation. Detailed immune monitoring data are not yet available. Conclusion: The results from this trial will help to understand how state of the art treatment could be complemented by cancer-testis antigen specific vaccines and immune-modulating drugs. The dynamics of host/tumor immune interaction during the conventional standard treatment will be analyzed to develop a strategy how and when specific immunotherapy should be added to the current treatment schedule. First results may be available at the time of presentation.